Comparative Effects of Whole-Body Vibration and Squatting Training on Balance and Mobility in Chronic Stroke Patients. A Randomized Controlled Trial - Attiya Irshad, Tahir Abbas, Sumaira, Muhammad Ijaz, Sobia Irshad, Atoofa Rasheed, Nayab John, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A stroke occurs when the central nervous system is disrupted by brain injury caused by a cerebrovascular hemorrhage, resulting in hemiparesis, nerve dysfunction, and muscular weakness but the use of innovative modalities for stroke is still unknown. The objective of this study is to investigate the comparative effects of whole-body vibration (WBV) training and squatting performance in chronic stroke patients. Methods: we reviewed 86 chronic stroke patients with the commencement of more than 6 months in physical therapy department of central park medical college, Lahore (2021-2022). An independent examiner randomized the patients individually after doing the baseline assessment. 86 ambulatory patients (51 men and 35 women) who are recruited in hospital. Results: During 2020-2021, 86 chronic stroke patients were investigated in hospital of whom all patients had a pre-existing medical condition like uncontrolled hypertension and diabetes. Total number of participants is N=86. Number of male participants N=25 and females N=18 in group A. Number of male participants in group B is 23 while number of females is 20. The participants in both groups demonstrated a significant increase in balance and mobility scores after 6 weeks of WBV training. Experimental group having 6th week BBS mean, standard deviation, 52.37, 1.92 and Control group having 6th week BBS mean, standard deviation 45.25, 4.18 respectively. The participants in both groups demonstrated a significant increase in balance and mobility scores after 6 weeks of WBV training but more pronounce results in experimental group. Conclusions: The results of this study concluded that whole-body vibration exercise with routine physical therapy treatment is very effective in improving balance, mobility, postural control, muscle strength, tone, power output, coordination reduced muscle spasticity and functional disability in patients with chronic stroke. Keywords: Whole-Body Vibration, Berg Balance Scale, Squats Exercise, Mechanical Vibrations